2020
DOI: 10.21203/rs.3.rs-28741/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive analyses reveal three-gene signatures in ovarian cancer

Abstract: Background: Ovarian cancer is a common cancer that affects the quality of women’s life. With the limitation of the early diagnosis of the disease, ovarian cancer has a high mortality rate worldwide. However, the molecular mechanisms underlying tumor invasion, proliferation, and metastasis in ovarian cancer remain unclear. We aimed to identify, using bioinformatics, important genes and pathways that may serve crucial roles in the prevention, diagnosis, and treatment of ovarian cancer. Methods: Three microarray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Li et al selected three microarray datasets (GSE14407, GSE36668, and GSE26712) for genome-wide gene expression profile analysis and identified MFAP2 as one of the differentially expressed genes between normal and ovarian cancer tissues. 12 In addition, Considine et al confirmed the overlapping genetic association signals between plasma protein levels of MFAP2 and EOC risk by using the regional genome map. 13 Based on this, we evaluated MFAP2 expression using the TCGA database of ovarian cancer cohort high-throughput RNA-sequencing data Gene Expression Profiling Interactive Analysis (GEPIA; http://gepia.cancer-pku.cn).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Li et al selected three microarray datasets (GSE14407, GSE36668, and GSE26712) for genome-wide gene expression profile analysis and identified MFAP2 as one of the differentially expressed genes between normal and ovarian cancer tissues. 12 In addition, Considine et al confirmed the overlapping genetic association signals between plasma protein levels of MFAP2 and EOC risk by using the regional genome map. 13 Based on this, we evaluated MFAP2 expression using the TCGA database of ovarian cancer cohort high-throughput RNA-sequencing data Gene Expression Profiling Interactive Analysis (GEPIA; http://gepia.cancer-pku.cn).…”
Section: Introductionmentioning
confidence: 95%
“…Li et al selected three microarray datasets (GSE14407, GSE36668, and GSE26712) for genome‐wide gene expression profile analysis and identified MFAP2 as one of the differentially expressed genes between normal and ovarian cancer tissues 12 . In addition, Considine et al confirmed the overlapping genetic association signals between plasma protein levels of MFAP2 and EOC risk by using the regional genome map 13 .…”
Section: Introductionmentioning
confidence: 99%